Damage assessment and recovery monitoring of the mangrove forests in Calauit island affected by typhoon Yolanda (Haiyan) - Malabrigo, Pastor L.; Umali, Arthur Glenn A.; Replan, Enrico L. (2016)
Calauit island is one of the islands in the Calamian Group of Islands in northern Palawan. The island is truly blessed with bountiful mangrove resources which provide the Tagbanuas enormous economic and ecological importance. Not known to many, Calauit island became the exit point of typhoon Yolanda causing tremendous damage to mangrove area. The study assessed the extent of damage and the recovery potential of Calauit mangrove forests from the devastation of Typhoon Yolanda. Ten sampling quadrats were established in areas where trees were observed to be 100% defoliated. Individual trees (> 1 cm diameter) inside each quadrat were measured and evaluated based on the assessment matrix developed in this study. Results of our assessment revealed serious damaged of mangroves in Calauit island. About 60% of the mangrove forests was severely affected by Typhoon Yolanda. Eight months after the typhoon, 21% of the trees have fully-recovered crown (all branches were able to develop leaves), 70% are still defoliate and 22% were already dead. Four of the 10 quadrats showed high potential for recovery as evidenced by a lot of seedlings (> 25 seedling recorded. Three monitoring plots were established for continuous monitoring of the recovery of the mangrove ecosystems. A course of actions was recommended to facilitate the recovery of mangroves in Calauit island, and to bring back the economic benefits from the forest.
Keywords: Mangrove ecology; Mangrove management; Calauit Island, Northern Palawan